Family-centered Outcomes that Matter Most to Parents: A Pediatric Feeding Disorders Qualitative Study. Issue 2 (August 2020) - Simione, Meg; Dartley, Anna Nicole; Cooper-Vince, Christine; Martin, Victoria; Hartnick, Christopher; Taveras, Elsie M.; Fiechtner, Lauren
ABSTRACT: Objective: The purpose of this study was to examine the perspectives of caregivers of children with feeding disorders. We sought to understand their child's feeding impairment through the lens of caregivers, including the impact impairments had on daily life and social participation, what outcomes matter most to caregivers, contextual determinants that affect achieving desired outcomes, and how treatment approaches can optimally support families. Methods: We interviewed caregivers of children, ages 2 to 5 years, who received care at the Center for Feeding and Nutrition at MassGeneral Hospital for Children in Boston, MA. All children had a feeding disorder diagnosis, defined as an impairment in oral intake. We analyzed interview transcripts using principles of immersion-crystallization. Results: We reached thematic saturation after interviewing 30 caregivers (25 female). 66.7% of the children were white, 13.3% Asian, 10.0% black, and 10.0% were more than 1 race. Thirty percent were Hispanic. We identified four themes: feeding impairments impact the daily life and social participation of children; improving their child's health and quality of life is most important to caregivers; child, caregiver, and community factors are facilitators of achieving desired outcomes; whereas time, financial, access, and knowledge factors are barriers; and caregivers prefer treatment approaches that incorporate principles of family-centered care. Conclusions: Given the daily life and social participation impacts of pediatric feeding disorders, treatment approaches should be family-centered, focus on functional and meaningful outcomes to improve the health and quality of life of children and their families, and address modifiable sociocontextual determinants.